Clinical Profile, Management, and Outcomes of Penile Fracture: A Case Series of Four Patients (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2025)
Background: Penile fracture is an uncommon urological emergency that requires prompt surgical management to prevent long-term complications such as erectile dysfunction and penile curvature. Material & Methods: We present a case series of four patients with penile fracture managed surgically at our institution. Patient demographics, clinical presentation, operative findings, surgical methods, and outcomes were analyzed.Results: The mean age was 45.7 years (range: 35–58). The duration from injury to presentation varied between 6 and 48 hours. Sexual intercourse was the most common cause (three cases, 75%), with one case resulting from accidental fall on an erect penis. All patients presented with penile pain, swelling, and immediate detumescence; two reported an audible 'snap'. Intraoperative findings revealed tunical tears in the right corpora cavernosa (n=2), left corpora cavernosa (n=1), and bilateral corpora cavernosa (n=1). Surgical repair was performed using subcoronal degloving in three patients and direct incision in one. No urethral injuries were noted. Postoperatively, one patient developed wound infection, managed conservatively. At follow-up, three patients had normal erectile function, while one developed mild penile curvature with preserved functional erections. Conclusion: Early surgical repair of penile fracture results in favorable outcomes. Our series reinforces the importance of prompt diagnosis and intervention to preserve sexual function.